IMPLIKASI YURIDIS PERJANJIAN PERKAWINAN YANG DIBUAT SELAMA DALAM IKATAN PERKAWINAN TERHADAP UTANG BERSAMA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 - Putri, Priesty Yustika; Djatmika, Prija; Puspitawati, Dhiana (Legality : Jurnal Ilmiah Hukum, 2018)
Under the provisions of Article 29 of Law Number 1 Year 1974 on Marriage, a marriage agreement may only be made before or at the time of marriage. However, after the Decision of the Constitutional Court Number 69/PUU-XIII/2015, marriage agreements may also be made during the period of marriage ties. The making of this marriage agreement certainly affects the joint property of husband and wife obtained in the marriage period before the marriage agreement is made. Including if the couple also has a debt together. This then raises problems related to debt settlement. The purpose of this study is to determine the juridical implications of marriage agreements made during the marriage bonds to the joint debt post-Decision of the Constitutional Court. This research is classified as normative juridical research using the concept of law and conceptual. The results of the study show that after the Decision of the Constitutional Court Number 69/PUU-XIII/2015, which stipulates that a marriage agreement may be made during the period of marriage bonds related to the responsibility of the joint debt repayment arising prior to the marriage agreement, the settlement may be contracted as per the second agreement the husband and wife. This is because there are no rules that prohibit the existence of such clauses to be set forth in the marriage agreement. However, if a marriage agreement in which the settlement of the joint debt will result in harm to a third party then the marriage agreement is not allowed, as regulated in Article 29 paragraph (4) Act 1/1974.